OVERWEIGHT IN ADOLESCENTS: FOOD INSECURITY AND MULTIFACTORIALITY IN SEMIARID REGIONS OF PERNAMBUCO - Santos,Natália Fernandes dos (2020)
ABSTRACT Objective: To investigate context of overweight adolescents from the semiarid and rural areas of Pernambuco, considering the multifactorial nature of the determinants of being overweight, and the food and nutritional insecurity conditions of the region. Methods: A population based cross-sectional study was conducted from September to October 2015. The nutritional status of adolescents was assessed by body mass index (BMI) and classified by the BMI/Age indicator, according to sex. To analyze the factors associated with being overweight, the variables were grouped into: socioeconomic, demographic, environmental, lifestyle, psychological, biological and food and nutritional security. Poisson regression was used to verify the association between being overweight and independent variables. Results: The prevalence of excessive weight found was 20.1%, namely: 13.4% overweight and 6.7% obese. After adjusting for the confounding variables, the variables: occupancy situation (rented house), alcohol consumption, food security and light food insecurity, body perception (overweight and obese) and age range (10 to 14 years), were associated with being overweight. High food and nutritional insecurity was identified in 80.4% of the population. The moderate and severe forms were more frequent, and precarious social conditions were still prevalent in the region. Conclusions: The prevalence of being overweight was high, exceeding the expected for a population with better living conditions. The determinants of being overweight were: alcohol consumption, occupancy situation, self-perceived weight, age and food security/mild food insecurity.